2022
DOI: 10.1093/eep/dvac016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis on congenital limb anomalies in 14 European nations: A geospatiotemporal and causal inferential study

Abstract: Background Cannabinoid exposure is increasing in some European nations. Europe therefore provides an interesting test environment for the recently reported link between cannabis exposure and congenital limb anomaly (CLA) rates (CLAR). Exponential genotoxic dose-response relationships make this investigation both intriguing and imperative. Methods Annual CLAR in 14 nations were from EUROCAT. Drug use rates were from European M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…This study is remarkable for its notable consistency with previous reports in animals [3][4][5] and with other epidemiological reports from Australia, Canada and the USA [8][9][10]119,120]. The results also greatly strengthen earlier bivariate reports from Europe and confirm results in the space-time context and formal causal inferential frameworks [119,121].…”
Section: Generalizabilitysupporting
confidence: 90%
“…This study is remarkable for its notable consistency with previous reports in animals [3][4][5] and with other epidemiological reports from Australia, Canada and the USA [8][9][10]119,120]. The results also greatly strengthen earlier bivariate reports from Europe and confirm results in the space-time context and formal causal inferential frameworks [119,121].…”
Section: Generalizabilitysupporting
confidence: 90%
“…There are various strengths and limitations to the present conceptualization. The strengths include the remarkable consistency across the many epidemiological studies, which clearly demonstrates the genotoxic harms of cannabis exposure in several different international jurisdictions, in relation to both the congenital anomalies [ 28 , 36 , 37 , 40 , 45 , 46 , 49 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] and cancer [ 22 , 23 , 24 , 25 , 26 , 30 , 41 , 232 ], and, indeed, now also in aging [ 53 , 54 ]. Similar results in many different studies are clearly mutually supportive and strengthen the overall quality of the body of evidence.…”
Section: Mechanisms Of Cannabinoid Genotoxicitymentioning
confidence: 98%
“…For the reader who is unfamiliar with this epidemiological literature, it should be pointed out that most of the modern epidemiological studies referred to are not just observational ecological studies of convenience which happen to show a particular association. Many of the best studies used a formal space–time analysis and the quantitative tools of causal inference to introduce a pseudo-randomized quasi-experimental paradigm from which it is entirely appropriate to invoke causal associations [ 28 , 36 , 37 , 40 , 45 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many papers demonstrate that the dose-response relationship of cannabinoids with both genomic mutagenicity and mitochondrial toxicity is strongly exponential [52][53][54][55][56]. Moreover, this exponentiation of the dose-response effect has been extended to epidemiological studies where it has been repeatedly demonstrated that the passage from the fourth to fifth quintile of cannabinoid exposure is accompanied by a discontinuous quantum jump in congenital anomaly rates [5,[57][58][59][60].…”
Section: Introductionmentioning
confidence: 98%